2021
DOI: 10.1016/j.lanwpc.2020.100087
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after sphincter preservation surgery or abdominoperineal resection for low rectal cancer (ASPIRE): A long-term prospective, multicentre, cohort study

Abstract: Background: The long-term effects of radical resection on quality of life may influence the treatment selection. The objective of this study was to determine whether abdominoperineal resection has a better effect on the quality of life than sphincter preservation surgery at 3 years after surgery Methods: This prospective, cohort study included patients who underwent radical resection for low rectal cancer. The primary outcomes were European Organisation for Research and Treatment of Cancer QLQ-C30 and CR38 qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
0
29
0
2
Order By: Relevance
“…1 This multimodality treatment, although effective in achieving tumor control, is associated with significant morbidity, with bowel, urinary, and sexual dysfunction that can impair patients' quality of life permanently. 2 In addition, many patients with distal rectal cancer are left with a permanent colostomy. 2 As most of the sequelae from the multimodality therapy are related to surgery, 3 there is a strong incentive to explore nonsurgical treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…1 This multimodality treatment, although effective in achieving tumor control, is associated with significant morbidity, with bowel, urinary, and sexual dysfunction that can impair patients' quality of life permanently. 2 In addition, many patients with distal rectal cancer are left with a permanent colostomy. 2 As most of the sequelae from the multimodality therapy are related to surgery, 3 there is a strong incentive to explore nonsurgical treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with low-lying rectal cancer, those who underwent APR had better social and cognitive function and less symptoms compared with SPS group in a prospective study 46 . In a newest RCT study, different result was found as SPS showed better sexual-urinary functions in male patients 47 . According to the long-term QoL analysis in this study, although SPS patients had higher body image score, cognitive and social function are not satisfactory and LARS related symptoms such as diarrhoea and constipation are prominent.…”
Section: Discussionmentioning
confidence: 98%
“…These subsequent studies may therefore be more relevant to current practice. Another study 49 published since completion of the search also identified no difference in global QoL; however, although patients who had undergone APE had lower preoperative QoL, this was not accounted for in the conclusion that patients should undergo restorative surgery for low rectal cancer.…”
Section: Discussionmentioning
confidence: 98%